Nomenclatural notes on Piper Linn. (Piperaceae) from India II - Mukherjee, Prasanta Kumar (Phytotaxa, 2018)
In continuation of the taxonomic study of the genus Piper from India (Mukherjee, 2017), eighty-four Piper names, reported from India, are considered here for their typification, identity, and nomenclature. The scrutiny led to the recognition of twenty-four species. Thirty-five synonyms are proposed as new ones out of sixty-one treated here. Lectotypes are designated for almost all the species recognised here together with their synonyms or basionyms. Holotypes are mentioned when applicable. Of particular mention are P. hookeri and P. sylvaticum with confused identities and lacking proper typification. Corrections are suggested to earlier lectotypifications for P. hymenophyllum and P. rhytidocarpum. Extension of distribution to India from Myanmar are recorded for three species: P. acutistigmum, P. leptostachyum and P. pothoides.